Hominin vertebrae and upper limb bone fossils from Sterkfontein Caves, South Africa (1998–2003 excavations). Issue 3 (23rd December 2018) - Pickering, Travis Rayne; Heaton, Jason L.; Clarke, R. J.; Stratford, Dominic
Abstract: Objectives: We provide descriptions and functional interpretations of 11 >2.0 Ma hominin vertebral and upper limb fossils from Sterkfontein. Materials and methods: We employed taphonomic methods to describe postmortem damage observed on the fossils. We used osteometric tools and measurements to generate quantitative descriptions, which were added to qualitative descriptions of the fossils. These observations were then interpreted using published data on the same skeletal elements from extant and extinct hominoid taxa. Results: Six of the fossils carry carnivore tooth marks. Two vertebrae show morphologies that are consistent with fully developed lordosis of the lumbar spine, but which are not completely consistent with bipedal loading of the same intensity and/or frequency as reflected in the lumbars of modern humans. A clavicle shows a combination of humanlike and apelike features, the latter of which would have endowed its hominin with good climbing abilities. When combined, analyses of fragmentary radius and ulna fossils yield more ambiguous results. Discussion: The new fossil collection presents a mix of bipedal and climbing features. It is unclear whether this mix indicates that all Sterkfontein hominins of >2.0 Ma were terrestrial bipeds who retained adaptations for climbing or whether the collection samples two differently adapted, coeval hominins, Australopithecus africanus and Australopithecus prometheus, both of which are represented at Sterkfontein by skull remains. Regardless, the significant frequency of tooth‐marked fossils in the sample might indicate that predation was a selection pressure that maintained climbing adaptations in at least some Sterkfontein hominins of this period.